Subashish Bhattacharjee and Goutam Karmakar (Eds), The City Speaks: Urban Spaces in Indian Literature. London and New York: Routledge, 2022. 328 pp. ISBN: 9781032110820.: Book Review - Rout, Deblina (SARE: Southeast Asian Review of English, 2023)
The City Speaks: Urban Spaces in Indian Literature investigates the urban literature of the subcontinent at the turn of the twentieth and twenty-first centuries, adopting a critical stance towards the study of narrative accounts of the ‘city’. The volume explores the longstanding and intricate relationship between Indian literature (in English) and urban spaces, evaluating the city as a “producer of narratives as well as a consumer” (7). Registering the representation of urban spaces as more than mere background settings for narratives, as the foreword mentions, the anthology attempts to read the ‘city’ as represented within “sociocultural and experiential spheres” in Indian contexts (xiii). As the editors, Subashish Bhattacharjee and Goutam Karmakar, note, cities serve as a record of the “momentum of cultural maturity, the evolution of thought, and the shifts in demographic realisations” that foreground the very formation of countries (9). Documenting cities as evolutionary metaphors for tracing the cultural historiography of the nation, the volume presents novel interpretive frameworks for analysing urban literature through a variety of mediums, including novels, poetry, drama, and non-fiction accounts.